2001
DOI: 10.1046/j.1365-2788.2001.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorder in adults with intellectual disability. 1: Prevalence of functional psychiatric illness among a community‐based population aged between 16 and 64 years

Abstract: The reported prevalence of psychiatric illness among adults with intellectual disability (ID) varies widely between  and %; however, many methodological problems exist. The aims of the present study were to establish the prevalence of functional psychiatric illness among adults with ID who live in the community, in order to compare the overall rate and types of psychiatric illness between the population with ID and the general population without ID, and to establish the risk factors associated with psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
260
7
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(286 citation statements)
references
References 30 publications
13
260
7
6
Order By: Relevance
“…Prevalence rates of mental health problems among people with intellectual disabilities (IDs) vary widely depending on the diagnostic criteria and assessments used, with recent estimates suggesting that between thirteen and forty percent of people with IDs are affected (Cooper, Smiley, Morrison, Williamson, & Allan, 2007;Deb, Thomas, & Bright, 2001;Emerson & Hatton, 2007). The high prevalence rates, when compared to the general population, can be partly explained by the genetic vulnerability of people with IDs, and disadvantageous life events such as stigmatisation and isolation (Clarke, 2003;Cooper et al, 2007;Emerson & Hatton, 2007;Hulbert-Williams & Hastings, 2008;Reiss & Benson, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates of mental health problems among people with intellectual disabilities (IDs) vary widely depending on the diagnostic criteria and assessments used, with recent estimates suggesting that between thirteen and forty percent of people with IDs are affected (Cooper, Smiley, Morrison, Williamson, & Allan, 2007;Deb, Thomas, & Bright, 2001;Emerson & Hatton, 2007). The high prevalence rates, when compared to the general population, can be partly explained by the genetic vulnerability of people with IDs, and disadvantageous life events such as stigmatisation and isolation (Clarke, 2003;Cooper et al, 2007;Emerson & Hatton, 2007;Hulbert-Williams & Hastings, 2008;Reiss & Benson, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…A study cohort comparing people with learning disabilities with the general population revealed significantly higher rates of phobic disorder in the former (Deb et al, 2001a). A literature review (Raghavan, 1997) revealed a similar if not higher prevalence of generalised anxiety disorder in people with learning disabilities.…”
Section: Cooray and Bakalamentioning
confidence: 98%
“…They are a heterogeneous, psychosocially disadvantaged and vulnerable group with a relatively higher prevalence of mental disorders (Borthwick-Duffy, 1994). Despite difficulties in the diagnosis and classification of psychiatric illnesses in this population (Fryers, 1997) there is ample evidence that anxiety disorders do occur (McNally & Ascher, 1987) and they are reported to be at least as common as in the general population, if not more so (King et al, 1994;Deb et al, 2001a).…”
mentioning
confidence: 99%
“…The service gap is particularly great in those suffering ID and co-occurring mental disorders (ID -MD) (Cooper, Smiley, Morrison, Williamson, & Allan, 2007a). The point prevalence of associated psychiatric disorders in ID is about 40% (including behavior problems) (Bailey, 2007;Cooper et al, 2007a;Deb, Thomas, & Bright, 2001) and an annual incidence of 8% has been reported . Although people with ID can suffer from the whole spectrum of psychiatric disorders, some are notably more common than in the general population.…”
mentioning
confidence: 99%
“…Among the most commonly associated diagnoses are nonaffective psychosis (Salvador-Carulla, Rodríguez-Blá zquez, Rodríguez, Pé rez-Marín, & Velasquez, 2000;Cooper et al, 2007b) and bipolar disorder (Cooper, Smiley, Morrison, Williamson, & Allan, 2007c). ID-MD is also frequently linked to problem behaviors, which have prevalence around 20% in this population (Deb et al, 2001;Holden & Gitlesen, 2004;Lowe et al, 2007). The concept of family burden was imported to the study of ID from the mental health field.…”
mentioning
confidence: 99%